Expansion and replication of the theory of vicarious help-seeking. (2nd April 2020) - Williams, Michael J.; Horgan, John G.; Evans, William P.; Bélanger, Jocelyn J.
ABSTRACT: Gatekeepers are those in a position to recognize, in others, potentially problematic presenting issues, and who are willing and able to connect those persons to relevant service providers. In the domain of violence prevention, they represent a network of those who can serve as 'first responders' with respect to helping those in need. Therefore, it is important to understand both the facilitators and inhibitors of gatekeeper intervention, or what has been termed 'vicarious help-seeking:' the intent to help others who appear in need of help, but who are not actively seeking help. The present set of studies demonstrated both an expansion of the theory of vicarious help-seeking and a replication of its original four tenets (Part 1). Part 2 examined how gatekeepers would prefer to intervene in a violence prevention context: their natural inclinations with respect to doing so. Part 3 examined reasons preventing gatekeepers from reaching out to a third-party for assistance. Part 4 further examined who – in addition to friends – might be most influential/effective, as gatekeepers.